Genome-wide characterization of R2R3-MYB gene family in Santalum album and their expression analysis under cold stress - Tang, Minqiang; Liu, Le; Hu, Xu; Zheng, Haoyue; Wang, Zukai; Liu, Yi; Zhu, Qing; Cui, Licao; Xie, Shangqian (Frontiers in Plant Science, 2023)
Sandalwood (Santalum album) is a high-value multifunctional tree species that is rich in aromatic substances and is used in medicine and global cosmetics. Due to the scarcity of land resources in tropical and subtropical regions, land in temperate regions is a potential resource for the development of S. album plantations in order to meet the needs of S. album production and medicine. The R2R3-MYB transcription factor family is one of the largest in plants and plays an important role in the response to various abiotic stresses. However, the R2R3-MYB gene family of S. album has not been studied. In this study, 144 R2R3-MYB genes were successfully identified in the assembly genome sequence, and their characteristics and expression patterns were investigated under various durations of low temperature stress. According to the findings, 31 of the 114 R2R3-MYB genes showed significant differences in expression after cold treatment. Combining transcriptome and weighted gene co-expression network analysis (WGCNA) revealed three key candidate genes (SaMYB098, SaMYB015, and SaMYB068) to be significantly involved in the regulation of cold resistance in S. album. The structural characteristics, evolution, and expression pattern of the R2R3-MYB gene in S. album were systematically examined at the whole genome level for the first time in this study. It will provide important information for future research into the function of the R2R3-MYB genes and the mechanism of cold stress response in S. album.